A Low-Cost High Precision Time Measurement Infrastructure for Embedded Mobile Systems - Köker, Kemal; Hielscher, Kai-Steffen; German, Reinhard (Sixth International Workshop on Robot Motion and Control (RoMoCo'07), 2007)
Simulation is frequently used to test the performance of embedded systems in different operating scenarios and is usually based on a system model that focuses on the relevant parts, e.g. the response time. The accuracy of the system model is very important to gain minimum divergences to the real world and therefore it has to be calibrated and validated multiple times. The quality of the calibration and validation process depends on the accuracy of the monitored data of a real system. As an example, hardware monitoring requires a specialized device with a built-in clock, which generates timestamps for signals observed at some system interfaces. This solution may provide precise timestamps but can only be applied to systems located in one place like in [1]. The software method generates required time stamps in software, but the accuracy is dependent on the systems' load [2]. © Springer-Verlag London Limited 2007.
UnivIS-Import:2015-04-16:Pub.2007.tech.IMMD.IMMD7.alowco

Performance Analyses of Embedded Real-time Operating Systems using High-precision Counters - Köker, Kemal; Membarth, Richard; German, Reinhard (Proc. 3rd Int. Conf. on Autonomous Robots and Agents, 2006)
UnivIS-Import:2015-04-16:Pub.2006.tech.IMMD.IMMD7.perfor_4